Coastal inundation multi-hazard analysis for a construction site in Malaysia. (2016) - Harbitz, Carl B.; Kaiser, Gunilla; Glimsdal, Sylfest; Jaedicke, Christian; Vafeidis, Athanasios T.; Göthlich, Stephan E.; Høydal, Øyvind Armand; Løvholt, Finn; Nadim, Farrokh
Coastal inundation due to multiple hazards was analysed for a potential manufacturing plant at the Batu Kawan Industrial Park in Penang state, Malaysia. The analysis accounted for river floods, rainfall and flash floods, cyclones, tides, storm surges, sea-level rise, and tsunamis. Earthquakes, volcanoes, and the effects of climate changes were also briefly evaluated. The proposed site elevation of 2.60 m LSD (land survey data level; 30 cm above mean sea level) will probably be reached by both the 100-year flood and the 100-year combined tide and storm surge. The flooding risk is low, but coincidence with storm surge or high tide will aggravate the situation. Sea level rise over the next 100 years is assumed less than 0.55 m. The relative level for the other hazards was found to be lower. A further comparison of the various hazard levels is not meaningful without considering also the consequences (i.e., the risk).